2021
DOI: 10.1002/mnfr.202000728
|View full text |Cite
|
Sign up to set email alerts
|

Milk and Dairy Products Intake Is Related to Cognitive Impairment at Baseline in Predimed Plus Trial

Abstract: Scope To examine the association between milk and dairy products intake and the prevalence of cognitive decline among Spanish individuals at high cardiovascular risk. Methods and results Cross‐sectional analyses are performed on baseline data from 6744 adults (aged 55–75 years old). Intake of milk and dairy products is estimated using a food frequency questionnaire grouped into quartiles. The risk of developing cognitive impairment is based on the Mini‐Mental State Examination (MMSE). A higher prevalence of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…A few studies have previously reported that consumption of cheese, despite its relatively high proportion of saturated fat, may have a protective effect on cognitive function. [11,[13][14][15][16]49] In the present study, cheese consumption showed a nonsignificant positive trend with GCF. Furthermore, yogurt intake was found to be inversely associated with VFT-a, suggesting a negative impact on verbal ability/executive function.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…A few studies have previously reported that consumption of cheese, despite its relatively high proportion of saturated fat, may have a protective effect on cognitive function. [11,[13][14][15][16]49] In the present study, cheese consumption showed a nonsignificant positive trend with GCF. Furthermore, yogurt intake was found to be inversely associated with VFT-a, suggesting a negative impact on verbal ability/executive function.…”
Section: Discussionmentioning
confidence: 65%
“…A recent cross‐sectional study conducted within the PREDIMED‐Plus cohort reported that participants who consumed a higher amount of dairy products had lower cognitive function based on MMSE score. [ 15 ] Other studies conducted in different countries have reported either no or positive associations of dairy consumption with cognitive function; however, most of these studies were cross‐sectional in design, therefore subject to potential reverse causation, and had high heterogeneity which may also partly explain the discrepancy. [ 12,13,16,47 ]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations